A study on syntactic and semantic features of dimensional expressions denoting unlimitedness in english and vietnamese - Lê, Hồ Thị Hòa (ĐHĐN., 2015)
The thesis has been carried out with an attempt to reach a profound understanding of DEsdU in English and Vietnamese. In the study, the notions of expressions and semantics - the study of meaning are presented and discussed in the theoretical framework on which DEsdU are collected, classified, described and analyzed. Thanks to the careful process of choosing the data and the effective methods of comparison and contrast, similarities and differences between DEsdU in English and DEsdU in Vietnamese in the survey in the view of syntax and semantics are revealed so that learners will have a better and more effective use of language in communication. As a result, some findings have been discovered. The role of DEsdU is not only denoting size, dimensions but also expressing quantity, time and degree in the most subtle and effective ways based on different writing styles of each author and different cultural features of each nation. The DEsdU appear in language as an expression, which makes a great contribution to the development of the vocabulary system, the diversity in syntax and the richness in semantics. Based on findings, some teaching implications have been put forward and some suggestions for further study are made for later studies of this problem.